Project bakunanays bakuna nang mga kabataan ugaliin nang anak ay di saklitin. - Acebuque, Jason Clement S.; Cuachon, Anna Nicole O.; Deala, Carl Laurence L.
Based on the 2016 accomplishment report of the Iloio Provincial Health Office (PHO) for School-Based Immunization (SBI), the municipality of Pavia performed 50.9% and 84.4% for Measles-Rubella (MR) and Tetanus-diptheria (Td), respectively. After reviewing the health record of the Municipal Health Office of Pavia, it was found that Ungka II Elementary School had the least compliance. This project aimed to reduce the high refusal rate in MR and Td vaccines from 32.0% to 0-10.0% among children in the barangay by the end of the field practice. To attain the goal of the project, the following strategic components were implemented: formation of a core group called ImmuniTeam, age-appropriate health education through Wastong BakUNAWA sessions, and promotive and up-to-date immunization campaigns. In addition, a mobile ImmuniStation was constructed and ImmuniStar charts were utilized during the BAKULILITS sessions with the children. The results of the pre-test showed that the mean percentage scores of the children before the intervention was 65% and after the intervention, post-test scores significantly increased to 82% mean score of the children (p value<0.05; 95% confidence level). The knowledge component of the pre-test and post-test for the parents and guardians resulted in a statistically significant 20% increase, resulting to 84% average mean score from the 64% prior to intervention (p value<0.05; 95% confidence level). The attitudes of the respondents registered a 6% increase, which is not statistically significant, resulting to a change in the mean percentage score from 70% to 76% (p value<0.05; 95% confidence level). The practices of the parents also showed a relative improvement from the pre-test results. Lastly, there was 100% compliance for the upcoming SBI at the end of the project implementation, as indicated in their consent forms. The team, therefore, effectively reduced the refusal rate for both the MR and Td vaccines from 32% to 0%.